- Nós, VOZ, elas: mulheres professoras narrando suas vivências de desigualdade de gênero e raça no curso de Direito da Universidade Federal do Maranhão - UFMA - ALMEIDA, Ana Carla de Melo (2022)
This research, based on the experience of Afro-descendant professors from the Law course at the Federal University of Maranhão (UFMA), on the Imperatriz and São Luís campuses, aims to understand how these professors experience gender and race inequalities in higher education, and what way these experiences are faced and overcome by them. The theoretical-methodological option was based on a set of decolonial and Afrocentric theorizations that value the subject subordinated by traditional historiography. It used narratives (BENJAMIN, 1985) as a theoretical methodological perspective of investigation, facilitating dialogue and greater approximation to the research subjects, aiming at the production of data as a craft communication tool, analyzed under the bias of Louro's teachings (2014) , Scott (1995), Oyěwùmí (2002) with regard to the Gender category; Almeida (2019), Machado (2019), Boakari (2013) and Gonzalez (1982) in relation to studies of Afro descendants and Race; and Akotirene (2019), Gonzalez (2011) and Crenshaw (2004) to discuss the intersectionality category. Still from the perspective of gender relations Louro (2018) and Saffiotti (2013) were important in understanding work situations and the feminization of the teaching profession that cross women's experiences. The results showed that the professors experience similar lives with regard to gender and race inequalities within the academy, an aspect that is also intrinsic to the Law course. The debates raised in this study are contributions for Law Course students to become professionals who value cultural, ethnic and gender diversities, decolonizing legal education, and making the Law course more fair and egalitarian, forming, thus, legal professionals more critical and consistent with the reality of Brazil, leading them to more questions and consequent changes in the legislative structures of Brazil.